The Assisi Think Tank Meeting and Survey of post MAstectomy Radiation Therapy after breast reconstruction: The ATTM-SMART report. Issue 4 (April 2018) - Aristei, Cynthia; Kaidar-Person, Orit; Tagliaferri, Luca; Arenas, Meritxell; Coles, Charlotte E.; Offersen, Birgitte V.; Frezza, Giovanni; Leonardi, Maria Cristina; Valentini, Vincenzo; Bourgier, Céline; Poortmans, Philip M.P.
Abstract: Purpose: To describe the current European practise on post-mastectomy radiation therapy (PMRT) in relation to breast reconstruction. Methods: A 21-item questionnaire was distributed online via Survey Monkey. Items referred to 1. general topics (country, centre, years of experience in breast cancer); 2. clinical decision making; 3. RT techniques and dosimetry; 4. dose fractionation. Results: 283 responses were received from 19 countries. Most responders worked in public health services and in academic institutions and had 5–20 years experience. Although many indicated they were consulted about the timing and type of breast reconstructive surgery, final decisions were most often made by surgeons. Immediate reconstruction with expander followed by RT and subsequently permanent reconstruction with prosthesis was recommended by 61.6% of responders. Most (48.4%) adviced a boost only when margins were close or involved with an another 17.7% recommending it in the presence of high-risk features (T3-T4, lympho-vascular involvement). Intensity modulated RT was rarely used by about two-thirds of responders, except when with 3D technique the dose constraints were not achieved or when regional lymph nodes were included. Almost 60% of responders did not use bolus/tissue equivalent material (TEM). The main indication for bolus/TEM use was skin involvement. The majority of responders used 1.8–2 Gy per fraction. Conclusions: The present survey highlighted controversial areas in clinical practise, confirming the uncertainties about the scheduling of PMRT and breast reconstruction.